Spatial distribution and source apportionment of nitrogen in typical plain river networks and bacterial community response - You, Aiju; Zheng, Qiaoxi; Yao, Pengcheng (Frontiers in Microbiology, 2025)
IntroductionThe Yubei plain river network (YPRN) is confined and has poor hydrodynamics, resulting in the accumulation of pollutants. Therefore, it is of great significance to explore the mechanisms by which different anthropogenic contamination sources-namely domestic, aquaculture, industrial, and agricultural-affect nitrogen content, as well as the composition of nitrifying, denitrifying, and other bacterial communities.MethodsThis study determined δ15N and δ18O by bacterial denitrification, and quantitatively evaluate the contribution of pollution source through MixSIAR. And the changes of the bacterial community were analyzed through 16S rRNA gene sequencing.ResultsThe concentration of total nitrogen (TN) revealed a distinct spatial pattern, with the industrial area demonstrating the highest levels, followed closely by the aquaculture area and the domestic and agricultural areas. The stable isotope analysis delineated three dominant pollution source areas within the study region: i) an industrial pollution dominant area, accounting for 55% of the pollutant load; ii) a domestic pollution dominant area (39%); and iii) an aquaculture pollution dominant area (43%). The industry pollution samples demonstrated the highest TN concentrations and the lowest NO3-/TN ratio. Strong nitrification activity under high dissolved oxygen (DO) in the study area was investigated using stable isotope analysis. Proteobacteria, Bacteroidetes, and Desulfobacteria were the dominant bacterial phyla in the study area. Notably, Malikia species with nitrate-reducing capabilities were significantly more abundant in the industrially pollution area compared to the other pollution areas.DiscussionThe diversity of nitrogen types characteristic of the domestic pollution area mediated bacterial selection pressures, favoring nitrogen cycling and amplifying functional gene abundance. This bacterial activity enhanced nitrogen cycle efficiency, ultimately reducing nitrogen concentrations. Bacterial analyses revealed marked divergence in both community composition and function across different pollution types. Particularly, ecological network analysis showed greater complexity and more network links in the aquaculture pollution area. Overall, the results revealed the impacts of different pollution sources on the ecological processes shaping river microbial communities and determined variations in bacterial diversity and nitrogen-cycling gene abundances.